Silver nanoparticles: influence of stabilizing agent and diameter on antifungal activity against Candida albicans and Candida glabrata biofilms - Monteiro, D. R. [UNESP]; Silva, S.; Negri, M.; Gorup, L. F.; de Camargo, E. R.; Oliveira, R.; Barbosa, Débora de Barros [UNESP]; Henriques, M. (Wiley-Blackwell, 2012)
Aim: The purpose of this work was to evaluate the size-dependent antifungal activity of different silver nanoparticles (SN) colloidal suspensions against Candida albicans and Candida glabrata mature biofilms.Methods and Results: The research presented herein used SN of three different average sizes (5, 10 and 60 nm), which were synthesized by the reduction of silver nitrate through sodium citrate and which were stabilized with ammonia or polyvinylpyrrolidone. Minimal inhibitory concentration (MIC) assays were performed using the microdilution methodology. The antibiofilm activity of SN was determined by total biomass quantification (by crystal violet staining) and colony forming units enumeration. MIC results showed that all SN colloidal suspensions were fungicidal against the tested strains at very low concentrations (0.4-3.3 mu g ml(-1)). With regard to biomass quantification, SN colloidal suspensions were very effective only against C. glabrata biofilms, achieving biomass reductions around 90% at a silver concentration of 108 mu g ml(-1). In general, all SN suspensions promoted significant log(10) reduction of the mean number of cultivable biofilm cells after exposure to silver concentrations at or higher than 108 mu g ml(-1). Moreover, the results showed that the particle size and the type of stabilizing agent used did not interfere in the antifungal activity of SN against Candida biofilms.Conclusions: This study suggests that SN have antifungal therapeutic potential, but further studies are still required namely regarding formulation and delivery means.Significance and Impact of the Study: SN may contribute to the development of new strategies for the improvement of oral health and quality of life particularly of the complete denture wearers.
Keywords: biofilms; Candida albicans; Candida glabrata; infection; silver nanoparticles